Transforming Growth Factor‐β and Axl Induce CXCL5 and Neutrophil Recruitment in Hepatocellular Carcinoma. Issue 1 (20th December 2018) - Haider, Christine; Hnat, Julia; Wagner, Roland; Huber, Heidemarie; Timelthaler, Gerald; Grubinger, Markus; Coulouarn, Cédric; Schreiner, Wolfgang; Schlangen, Karin; Sieghart, Wolfgang; Peck‐Radosavljevic, Markus; Mikulits, Wolfgang
Abstract : Transforming growth factor (TGF)‐β suppresses early hepatocellular carcinoma (HCC) development but triggers pro‐oncogenic abilities at later stages. Recent data suggest that the receptor tyrosine kinase Axl causes a TGF‐β switch toward dedifferentiation and invasion of HCC cells. Here, we analyzed two human cellular HCC models with opposing phenotypes in response to TGF‐β. Both HCC models showed reduced proliferation and clonogenic growth behavior following TGF‐β stimulation, although they exhibited differences in chemosensitivity and migratory abilities, suggesting that HCC cells evade traits of anti‐oncogenic TGF‐β. Transcriptome profiling revealed differential regulation of the chemokine CXCL5, which positively correlated with TGF‐β expression in HCC patients. The expression and secretion of CXCL5 was dependent on Axl expression, suggesting that CXCL5 is a TGF‐β target gene collaborating with Axl signaling. Loss of either TGF‐β or Axl signaling abrogated CXCL5‐dependent attraction of neutrophils. In mice, tumor formation of transplanted HCC cells relied on CXCL5 expression. In HCC patients, high levels of Axl and CXCL5 correlated with advanced tumor stages, recruitment of neutrophils into HCC tissue, and reduced survival. Conclusion: The synergy of TGF‐β and Axl induces CXCL5 secretion, causing the infiltration of neutrophils into HCC tissue. Intervention with TGF‐β/Axl/CXCL5 signaling may be an effective therapeutic strategy to combat HCC progression in TGF‐β‐positive patients.